SIMULATION TECHNIQUES FOR ANALYZING THE HEXA ALLEN WRENCH (International Journal of Food and Nutritional Sciences, 2022)
This is a small handheld tool used for turning bolts and screws which have hexagonal sockets. Many people assume that Allen keys are new, but to surprise, these tools are fairly old. The concept of a hexagonal-shaped screwdriver came in the mid-to-late 1800s and became popular. Now they are available in different sizes. According to our research, the existing products have a lot of problematic issue compared to our product. One of the most common problems we found are the existing products doesn’t have a storage space and little bit heavy. When compared to our products, we provide a very small allen key. Our product is not only easy to use, but they also can give too many benefits to our buyers. Methodology is a method and technique for designing, collecting and analyzing data to produce evidence that supports a study. I hope my project can reduce the burden on users. Totally we are using exisisting Aluminum round bars, Stainless steels & mild steel round barsalong with advanced SAE-AISI 6150, Alloy Heavy Duty Steel 304 and AISI 8650 materials.3D parametric model of hexaallen key developed by using SOLIDWORKS workbench and analyzed statically using ANSYS 18.0 workbench. Finally recommended which material is better for mechanical behavior and end user point of view